Productivity Test Soil Latosol Reddish brown Landslide Vulnerability Through Study Influence Dosage Cow Manure and Intensity of Soil Cultivasion Against Growth and Sweet Corn Results - Priyono, Rahayu, S Minardi dan Suntoro (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
-